Gen-Z Youth in The Shadow of Drugs - Faridatul Lailiyah; Zahara Nabila; Chrisnawanto Nugroho (Institut Agama Islam Al-Fatimah Bojonegoro, 2024)
This research aims to find out and analyze (1) the extent to which gen-z teenagers are overshadowed by the social phenomenon of drug abuse in their social environment; (2) education about the dangers of drugs for the lives of gen-z teenagers; and (3) supporting the drug-free gen-z campaign for Golden Indonesia 2045. This research uses a qualitative method, located in West Surabaya, and analyzes the dramaturgy theory by Erving Goffman. The results showed that Gen-Z adolescents are in the shadow of drugs, as seen from the process of introduction to drugs divided into two groups in their daily lives, namely the user group and the non-user group. To play themselves in the social environment, the five informants in this study practiced things according to the dramaturgy theory of front stage and backstage. The behavior shown by the five informants during the front stage is to maintain the best possible attitude so as not to be seen as a drug user by showing, manipulating, and regulating behavior in such a way as to blend in and look like a normal teenager so that their existence can be accepted by their social environment. On backstage, the five informants in this study show a freer personality; their original character is seen; they do not play a role; they even have a very different side when they are on the front stage, namely being more joking, socially active, and becoming a person who is easily provoked by emotions. It is hoped that through this paper, Gen-Z youth will be more careful in choosing friendships and social environments and be good at filtering all available information as an impact of globalization